The Life Of Abraham Lincoln - Arnold, Isaac N. (Lincoln University of Nebraska Press, 1994)
Abraham Lincoln "was a tall, spare man, with large bones, and towering up to six feet and four inches. He leaned forward, and stooped as he walked ... There was no grace in his movements, but an expression of awkwardness, combined with force and vigor.
Keywords: Lincoln, Abraham, -- 1809-1865. Lincoln, Abraham, -- 1809-1865 Presidents -- United States -- Biography